2018
DOI: 10.1111/cfs.12586
|View full text |Cite
|
Sign up to set email alerts
|

Family contact in foster care in Portugal. The views of children in foster care and other key actors

Abstract: This is a pilot study on the sensitive issue of how children and young people experience family contact in foster care, and the views of key adults in their lives on the same issue. There is a special focus on the children's experiences, opinions, and feelings. The study is a response to the relative scarcity of literature on family contact based on the experiences of children and adults in caring roles. This is a qualitative and exploratory study, with a sample of 10 children and young people in care in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…These complement the literature that stressed the importance of social capital ( Hook and Courtney, 2011 ; Skobba et al, 2018 ), that is also confirmed in our work highlighting the importance of peers and community involvement. This additional support received not only from biological and foster families, could promote the strengthening of identity and the reduction of feelings of loss and rejection ( Delgado et al, 2019 ; Wissö et al, 2019 ). Romantic relationships become a central theme in the transition to adulthood ( Oudekerk et al, 2015 ), and even though the early relationships in the biological family, these youth seem to develop some ability to manage autonomy and related challenges in adult relationships across different social domains (romantic relations, friendship, family).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These complement the literature that stressed the importance of social capital ( Hook and Courtney, 2011 ; Skobba et al, 2018 ), that is also confirmed in our work highlighting the importance of peers and community involvement. This additional support received not only from biological and foster families, could promote the strengthening of identity and the reduction of feelings of loss and rejection ( Delgado et al, 2019 ; Wissö et al, 2019 ). Romantic relationships become a central theme in the transition to adulthood ( Oudekerk et al, 2015 ), and even though the early relationships in the biological family, these youth seem to develop some ability to manage autonomy and related challenges in adult relationships across different social domains (romantic relations, friendship, family).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that besides a vulnerability and adversity that youth frequently experience following aging out of foster care, positive relationships may buffer the negative outcomes succeeding emancipation ( Greeson and Bowen, 2008 ). Foster research has emphasized the need for caring relationships to be maintained in the lives of individuals in the transition to adulthood, showing the beneficial effects of caring relationships such as the strengthening of identity, the reduction of feelings of loss and rejection, and the promotion of self-esteem ( Delgado et al, 2019 ; Wissö et al, 2019 ; Ball et al, 2021 ). Alongside, relationships with the family of origin, with others, romantic relationships, as well as affective experiences play a key-role on positive outcomes of American emancipated foster youth ( Tyrell and Yates, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Data collection focused on two published articles (Delgado et al, 2018;Carvalho et al, 2020), three books (Delgado, 2007;Delgado et al, 2013;Delgado et al, 2016), one thesis (Diogo, 2018) and two dissertations (Batalhas, 2008;Gonçalves, 2017) addressing the experiences of main actors in foster care. The main characteristics of the selected studies are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…It is important to understand that children are endowed with wisdom and a view of the world which are important elements to be taken into consideration when assessing their subjective living (Bernardi, 2010). One of the main forms to assess the real needs of children and adolescents who live in institutional sheltering is giving them the right to speak up, in a way they can report their own feelings and perspectives (Bernardi, 2010;Delgado et al, 2019;Gabatz et al, 2010). It is also crucial to highlight that for the child to be able to give their opinion about what would be the best for them, it is imperative that they are aware of their own situation, in other words, without really understanding the reality they are inserted, they are not able to provide a substantiated opinion (Oliveira, 2015).…”
Section: Introductionmentioning
confidence: 99%